Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine which of the given functions is even, we need to verify if [tex]\( g(x) = g(-x) \)[/tex] for each function.
1. [tex]\( g(x) = (x-1)^2 + 1 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = ((-x) - 1)^2 + 1 = (-x - 1)^2 + 1 \][/tex]
[tex]\[ = (x + 1)^2 + 1 \][/tex]
[tex]\[ = x^2 + 2x + 1 + 1 \][/tex]
[tex]\[ = x^2 + 2x + 2 \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = x^2 - 2x + 1 + 1 \][/tex]
[tex]\[ = x^2 - 2x + 2 \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
2. [tex]\( g(x) = 2x^2 + 1 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x)^2 + 1 = 2x^2 + 1 \][/tex]
Since [tex]\( g(x) = g(-x) \)[/tex], this function is even.
3. [tex]\( g(x) = 4x + 2 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 4(-x) + 2 = -4x + 2 \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 4x + 2 \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
4. [tex]\( g(x) = 2x \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x) = -2x \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
Upon evaluation, only the function [tex]\( g(x) = 2x^2 + 1 \)[/tex] is even. Therefore, the correct answer is [tex]\( \boxed{2} \)[/tex].
1. [tex]\( g(x) = (x-1)^2 + 1 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = ((-x) - 1)^2 + 1 = (-x - 1)^2 + 1 \][/tex]
[tex]\[ = (x + 1)^2 + 1 \][/tex]
[tex]\[ = x^2 + 2x + 1 + 1 \][/tex]
[tex]\[ = x^2 + 2x + 2 \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = x^2 - 2x + 1 + 1 \][/tex]
[tex]\[ = x^2 - 2x + 2 \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
2. [tex]\( g(x) = 2x^2 + 1 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x)^2 + 1 = 2x^2 + 1 \][/tex]
Since [tex]\( g(x) = g(-x) \)[/tex], this function is even.
3. [tex]\( g(x) = 4x + 2 \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 4(-x) + 2 = -4x + 2 \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 4x + 2 \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
4. [tex]\( g(x) = 2x \)[/tex]
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x) = -2x \][/tex]
Compare this with [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x \][/tex]
Since [tex]\( g(x) \neq g(-x) \)[/tex], this function is not even.
Upon evaluation, only the function [tex]\( g(x) = 2x^2 + 1 \)[/tex] is even. Therefore, the correct answer is [tex]\( \boxed{2} \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.